Use Case and Requirements Analysis in a Remote Rural Context in Mali - and Bon, Anna; de Boer, Victor; Gyan, Nana Baah; van Aart, Chris; De Leenheer, Pieter; Tuyp, Wendelien; Boyera, Stephane; Froumentin, Max; Grewal, Aman; Allen, Mary; Tangara, Amadou; Akkermans, Hans (Requirements Engineering: Foundation for Software Quality, 2013)
[Context & motivation] Few studies have reported on a systematic use case and requirements analysis of low-tech, low-resource contexts such as rural Africa. This, despite the widespread agreement on the importance of Information and Communication Technologies (ICT) for social and rural development, and despite the large number of ICT projects targeting underprivileged communities. [Question/problem] Unfamiliarity with the local context and differences in cultural and educational backgrounds between end-users and software engineers are the challenges for requirements engineering (RE) we encountered. [Principal ideas/results] We describe a systematic approach to RE in developing areas, based on the Living Lab methodology. Our approach is supported by extensive field research and based on co-creation within a multi-disciplinary and multi-cultural team of developers and users. This approach creates a shared understanding of the problem and its local context, and optimizes communication. [Contribution] We illustrate the approach using a case study of web- and voice-based communication services, that we developed for a rural context in Mali.